Study of the prevalence of Salmonella Arizonae infection in backyard and commercial turkey flocks in Golestan, Mazandaran, Gilan, and Tehran provinces - Khalilzadeh, Mahdi; Peighambari, Seyed Mostafa; Akbarein, Hesameddin (Journal of Poultry Sciences and Avian Diseases, 2023)
Arizona infection or avian arizonosis (AA) is an acute or chronic egg-transmitted disease of primarily young turkey poults characterized by septicemia, neurological signs, blindness, and increased mortality, caused by caused by the bacterium Salmonella enterica subsp. Arizonae  (S. Arizonae ). This study investigated the infection rate of Salmonella Arizonae in backyard and commercial turkeys of Golestan, Mazandaran, Gilan, and Tehran provinces. Fecal samples taken from industrial and backyard turkeys were transferred to cysteine selenite enrichment medium, incubated at 37° C for 24 hours, and then cultured linearly in selected media of Chromagar, Salmonella-Shigela, XLD, and McConkey agar plates and exposed to 37° C for 24 hours. Suspected Salmonella colonies were cultured in differentiated TSI and urea medium for confirmation and incubated at 37° C for 24 h. In this study, the microbial culture method was used by pre-enrichment, specific, and differential media to determine the level of contamination of backyard and industrial turkey flocks in four provinces of Golestan, Mazandaran, Gilan, and Tehran. All samples were tested for Salmonella infection, but positive samples were not found for Salmonella. Only 22 specimens were infected with Proteus. Our information about the Iranian turkey industry is limited compared to worldwide studies. This may be due to Iran's less widespread use of turkey production. The non-isolation of Salmonella in this study is inconsistent with some of the few studies in the country, which may be due to differences in the type of sampling, geographical location, and materials and methods of work. Due to the growth of the turkey industry in the country, the importance of studying Salmonella and other pathogens is felt more than ever.